Paradigma Kesejahteraan Sosial Islam: Tinjauan Sejarah Praktik Pemerintahan Umar bin Khattab - Tri Ahmad Faridh (Universitas Darussalam Gontor, 2022)
AbstractThis study aims to explain the paradigm of social welfare in Islam, especially that which has been practiced in the history of Umar bin Khattab's government. This study is a qualitative study with a literature study approach. Meanwhile, the data analysis uses Miles and Huberman's model analysis, which the data will be reviewed with modern social welfare paradigms, such as the residual paradigm, the institutional paradigm, and the developmental paradigm. The results of the study show that the Islamic social welfare paradigm during the reign of Umar bin Khattab fits into the developmental paradigm, which has also used by ideal pilot countries for the social welfare sector. Caliph Umar had a welfare system and institution, baitul mal and diwan-diwan which regularly, permanently and proactively provided universal social welfare assistance and services for all members of society, including for non-Muslims. Caliph Umar's social welfare development efforts were not only curative, short-term and emergency consumption aimed at disadvantaged groups, but there were also efforts to promote a kind of social insurance. Caliph Umar also was implementing universal public policies, making social investments and comprehensive socio-economic development. This Islamic social welfare paradigm is based on the principle of cooperation, social solidarity, and the principle of socio-economic justice for all members of society. All of them also is based on spirituality, responsibility towards Allah and awareness of the hereafter.Keywords: Social Welfare, Umar bin Khattab, Residual Paradigm, Institutional Paradigm, Developmental Paradigm AbstrakKajian ini bertujuan untuk memaparkan paradigma kesejahteraan sosial dalam Islam, khususnya yang telah dipraktikkan dalam sejarah pemerintahan Umar bin Khattab. Kajian ini adalah kajian kualitatif dengan pendekatan studi pustaka. Adapun analisis data menggunakan analisis model Miles and Huberman, dengan mengkaitkan data temuan dengan teori paradigma-paradigma kesejahteraan sosial modern seperti paradigma residual, paradigama institusional dan paradigma developmental. Hasil kajian menunjukkan paradigma kesejahteraan sosial Islam di masa pemerintahan Umar bin Khattab sejurus dengan paradigma developmental, yang juga dipakai di negara-negara percontohan ideal di bidang kesejahteraan sosial modern. Khalifah Umar telah memiliki sistem dan lembaga kesejahteraan berupa baitul mal dan diwan-diwan yang secara reguler, permanen dan mapan proaktif menyediakan bantuan dan layanan kesejahteraan sosial secara universal bagi segenap anggota masyarakat, termasuk bagi non-muslim. Usaha pembangunan kesejahteraan sosial Khalifah Umar tak hanya yang bersifat konsumsi kuratif, jangka pendek dan darurat yang ditujukan kepada kelompok-kelompok tak mampu saja, namun juga ada usaha untuk memajukan semacam asuransi sosial, selain juga melaksanakan kebijakan-kebijakan publik yang universal, melakukan investasi sosial dan pembangunan ekonomi-sosial yang komprehensif. Paradigma kesejahteraan sosial Islam ini dilandasi oleh prinsip kerjasama, solidaritas sosial, serta prinsip keadilan sosial-ekonomi bagi semua anggota masyarakat yang dilandasi atas tanggungjawab spiritual terhadap Allah dan keakhiratan.Kata kunci: Kesejahteraan Sosial, Umar bin Khattab, Paradigma Residual, Paradigama Institusional, Paradigma Developmental